2001
DOI: 10.1021/jp0101918
|View full text |Cite
|
Sign up to set email alerts
|

DFT Calculations for Cu-, Ag-, and Au-Containing Molecules

Abstract: The physicochemical properties of a set of molecules containing Cu, Ag, or Au atoms were calculated using the GAUSSIAN program suite, with the purpose of investigating the various density functional theory (DFT) approaches for subsequent application in cluster calculations. The test set comprised the copper-based molecules CuH, CuO, CuS, Cu2, CuCl2 -, CuCH3, CuC2H2, Cu2(HCO2)4(H2O)2, and Cu6H6(PH3)6 and the silver and gold diatomics AgH, AgO, AgS, Ag2, AgCu, AuH, AuO, AuS, Au2, AuCu, and AuAg. The DFT methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 54 publications
5
59
0
2
Order By: Relevance
“…The present B3LYP predictions of the adiabatic ionization potential, electron affinity, dissociation energy, and bond distance are 8.64 eV, 1.43 eV, 1.91 eV, and 2.599 , respectively, which are close to the corresponding experimental values of < 9.15 eV, 1.31 eV, 2.08 AE 0.1 eV, 2.53 [11,12] and comparable to those of previous DFT calculations. [11] It is also noted that these values are in between Figure 1.…”
Section: Agausupporting
confidence: 88%
See 1 more Smart Citation
“…The present B3LYP predictions of the adiabatic ionization potential, electron affinity, dissociation energy, and bond distance are 8.64 eV, 1.43 eV, 1.91 eV, and 2.599 , respectively, which are close to the corresponding experimental values of < 9.15 eV, 1.31 eV, 2.08 AE 0.1 eV, 2.53 [11,12] and comparable to those of previous DFT calculations. [11] It is also noted that these values are in between Figure 1.…”
Section: Agausupporting
confidence: 88%
“…For inorganic or organic molecules binding to the gold-silver clusters, the chemical bonding depends strongly on the property of the unoccupied orbital in the metallic cluster. [12,13] Mitric et al studied the catalytic oxidation of CO and O 2 adsorbed on mixed silver-gold clusters with respect to the role of CT in the catalytic activity of AgAu À . [2] Chretien et al studied the adsorption of propene on mixed gold-silver clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The standard basis set 6‐311G(d, p) is used for C and H atoms while Lanl2dz ECP32 basis set is adopted for Ag and Au atoms. It has been shown that these theoretical methods are currently the most accurate and appropriate approach for studying the structure and energy of organo‐coinage metal molecules or the coinage metal cluster 33–38. All transition states are located without imposing any constraints during the geometry optimization process and are confirmed by one imaginary mode from vibrational analysis calculations.…”
Section: Methodsmentioning
confidence: 98%
“…Free Ag 2 , Au 2 and AgAu particles have been previously investigated by Legge et al [32] using different DFT functionals and Gaussian functions. This methodology predicts a Ag-Ag bond relatively weaker than Au-Au and Ag-Au, a fact in agreement with experimental measurements.…”
Section: Resultsmentioning
confidence: 99%